Interventions to combat or prevent drug counterfeiting: a systematic review. Issue 3 (18th March 2015) - El-Jardali, Fadi; Akl, Elie A; Fadlallah, Racha; Oliver, Sandy; Saleh, Nadine; El-Bawab, Lamya; Rizk, Rana; Farha, Aida; Hamra, Rasha
Abstract : Objective: Drug counterfeiting has serious public health and safety implications. The objective of this study was to systematically review the evidence on the effectiveness of interventions to combat or prevent drug counterfeiting. Data sources: We searched multiple electronic databases and the grey literature up to March 2014. Two reviewers completed, in duplicate and independently, the study selection, data abstraction and risk of bias assessment. Study eligibility criteria, participants and interventions: We included randomised trials, non-randomised studies, and case studies examining any intervention at the health system-level to combat or prevent drug counterfeiting. Outcomes of interest included changes in failure rates of tested drugs and changes in prevalence of counterfeit medicines. We excluded studies that focused exclusively on substandard, degraded or expired drugs, or that focused on medication errors. Appraisal and synthesis: We assessed the risk of bias in each included study. We reported the results narratively and, where applicable, we conducted meta-analyses. Results: We included 21 studies representing 25 units of analysis. Overall, we found low quality evidence suggesting positive effects of drug registration (OR=0.23; 95% CI 0.08 to 0.67), and WHO-prequalification of drugs (OR=0.06; 95% CI 0.01 to 0.35) in reducing the prevalence of counterfeit and substandard drugs. Low quality evidence suggests that licensing of drug outlets is probably ineffective (OR=0.66; 95% CI 0.41 to 1.05). For multifaceted interventions (including a mix of regulations, training of inspectors, public-private collaborations and legal actions), low quality evidence suggest they may be effective. The single RCT provided moderate quality evidence of no effect of 'two extra inspections' in improving drug quality. Conclusions: Policymakers and stakeholders would benefit from registration and WHO-prequalification of drugs and may also consider multifaceted interventions. Future effectiveness studies should address the methodological limitations of the available evidence. Trial registration number: PROSPERO CRD42014009269.